2018
DOI: 10.3390/inventions3030065
|View full text |Cite
|
Sign up to set email alerts
|

PDMS-Based Microfluidic Devices for Cell Culture

Abstract: Microfluidic technology has affirmed itself as a powerful tool in medical and biological research by offering the possibility of managing biological samples in tiny channels and chambers. Among the different applications, the use of microfluidics for cell cultures has attracted much interest from scientists worldwide. Traditional cell culture methods need high quantities of samples and reagents that are strongly reduced in miniaturized systems. In addition, the microenvironment is better controlled by scaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 72 publications
0
68
0
Order By: Relevance
“…Initially, the cells can be cultured for several days in the microdevice after injection, permitting adaptation to the new environment. Microdevice is fabricated from a gaspermeable polymer that has been proven as biocompatible for both plant 9 and animal cells 11,12 . According to our data, shallow microfluidic channels are as efficient as coverslips to flatten cells for HILO imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the cells can be cultured for several days in the microdevice after injection, permitting adaptation to the new environment. Microdevice is fabricated from a gaspermeable polymer that has been proven as biocompatible for both plant 9 and animal cells 11,12 . According to our data, shallow microfluidic channels are as efficient as coverslips to flatten cells for HILO imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Microfluidic devices are commonly fabricated from polydimethylsiloxane (PDMS), a biocompatible material suitable for long-term culture conditions [9][10][11][12] . PDMS can be moulded into different designs and patterns; for example, a recent study using microdevice has demonstrated that tip-growing plant cells are able to penetrate extremely narrow 1-µm gaps 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Polydimethylsiloxane (PDMS) is the preferred material for making microuidic devices due to its long history, ease of use, gas permeability, and relative low cost. 25,26 However, these devices experience problems with lab-to-lab reproducibility and can be time consuming to make. PDMS is also gas permeable, which has advantages for oxygen diffusion into cell culture media but presents problems for long term cell culture where media evaporation can lead to osmolality shis and possible complications with cell culture.…”
Section: Introductionmentioning
confidence: 99%
“…PDMS is also gas permeable, which has advantages for oxygen diffusion into cell culture media but presents problems for long term cell culture where media evaporation can lead to osmolality shis and possible complications with cell culture. 26,27 Additionally, the uncured monomer can leach into the cell culture media or small molecules can diffuse into the material making analyte analysis difficult. 26,28 To combat the complications presented by PDMS, microuidic devices have also been made out of thermo plastics and glass, although each presents challenges in fabrication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation